Prevalence of Hypertension in Patients with Coronary Artery Diseases with and without Type-II Diabetes Mellitus - Mishra Mritunjay; DVSS Ramavataram; Tejas Shah; Trushna Shah (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: - Hypertension is one of the major public health issue and also have an important area ofresearch. Its high prevalence and being a major risk factor for cardiovascular diseases and other complications.Hypertension accounts for the majority of hypertension in individuals with diabetes, particularly those withType-2 diabetes.Objectives. To study association of hypertension with diabetes and also find out the prevalence ofhypertension in type-II diabetes, CAD patients with or without type-II diabetes mellitus.Materials & Methods: - It is a type of case control study among the rural population of kamothe, whereA total of 120 subjects were included in the study among which 90 were in study subjects and 30 were incontrol groups and among the study subjects (i.e.-90) 30 were in CAD with diabetes, 30 were in CAD and30 in Diabetes mellitus respectively. BMI was calculated by height and weight and BP was recorded. Bloodsugar were measured by enzymatic method on EM-200 analyzerResults:-The mean level of BMI in the group –II that is in the coronary artery disease with diabetes is24.22 ± 1.0, in only coronary artery diseases was 20.65 ± 2.0 and in only diabetes subjects was 24.39±1.0of the study subjects in the comparison of control subjects i.e. 23.17 ± 1.78 and we have also found thestatistical significance (P-0.001) in all the study groups. In the aspects of Blood pressure distribution, wehave distributed it into different stage of hypertension and found that more number of patients from groupIII i.e. only CAD and found 83% diastolic BP in pre hypertension stages and 60% were hypertensive andin only DM, there were 56% SBP and 60% DBP in pre-hypertensive.Conclusion: - Periodic evaluation of patient with pre hypertension and hypertension by applying lifestyle modifications and may favor the good outcome and also prompt the treatment of hypertension andhyperglycemia.